Pengaruh Penerapan Green Accounting, Pengungkapan Lingkungan dan Material Flow Cost Accounting (MFCA) Terhadap Profitabilitas Perusahaan (Studi Pada Perusahaan Sektor Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2019) - Asti Asti (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2021)
This study intends to examine the effect of the application of green accounting, environmental disclosure and material flow cost accounting on company profitability. Profitability is measured using Return On Assets (ROA), it can be seen that the profitability of various industrial sector companies listed on the IDX in 2015-2019 has an unstable value. The population in this study were all companies in the various industrial sectors listed on the IDX during the 2015-2019 period. The sampling technique used purposive sampling method. The results of this study indicate that the simultaneous application of green accounting, environmental disclosure and material flow cost accounting have an effect on company profitability. The results of this study also show that the application of green accounting and environmental disclosure partially affect the company's profitability, while the material flow cost accounting partially does not affect the company's profitability. The goal of each company is to increase the amount of profitability. However, at this time the company is not only asked to maximize profits but can be responsible for the environmental impact caused by its operational activities.